A Critical Analysis of Scenarios for Small and Medium Enterprisee in NAFTA renegotiations; Un Anaĺisis Crit́ico de los Escenarios para pequen\~as y medianas empresas en las Renegociaciones de NAFTA - JoseǴ Vargas-Hernańdez; Elsa Patricia Orozco Quijano; Jorge Virchez (Small Business International Review (SBIR), 2019)
The aim of this paper is to set some scenarios for small and medium enterprises (SMEs) from a critical analysis of the provisions in the North American Free Trade Agreement (NAFTA) renegotiation, its challenges and opportunities. The critical analysis departs from the questionable position of the withdrawal from NAFTA and their consequences for SMEs of not giving continuity through a process of renegotiation among the three partners. The method used is the critical analysis based mainly in some sources of information, analysis of results of NAFTA, and the strategic examination of its challenges and opportunities for SMEs. Finally, the analysis establish some possible scenarios post-NAFTA renegotiation and some strategic proposals for the SMEs. – – El objetivo de este documento es establecer algunos escenarios para las pequen\~as y medianas empresas (PYMEs) a partir de un anaĺisis crit́ico de las disposiciones en la renegociacioń del Tratado de Libre Comercio de Ameŕica del Norte (NAFTA), sus desafiós y oportunidades. El anaĺisis crit́ico parte de la cuestionable posicioń de la retirada del NAFTA y sus consecuencias para las PYMEs de no dar continuidad a traveś de un proceso de renegociacioń entre los tres socios. El met́odo utilizado es el anaĺisis crit́ico que se basa principalmente en algunas fuentes de informacioń, el anaĺisis de los resultados del NAFTA y el examen estrateǵico de sus desafiós y oportunidades para las PYME. Finalmente, el anaĺisis establece algunos escenarios posibles despueś de la renegociacioń del NAFTA y algunas propuestas estrateǵicas para las PYMEs.
Keywords: SMEs; F1; F6; L0; 650; challenge; NAFTA; opportunity; renegotiation; scenario; desafió; NAFTA; oportunidad; renegociacioń; escenario; PYMEs